Small gardens for city and country : a guide to designing and planting your green spaces - Ireys, Alice Recknagel (New Jersey : Prentice-Hall, 1978)
The purpose of this book is to give ideas and suggestion for small gardens in city and country. Gardens have different meanings for each of us, but for everyone the completed garden is an experience to enjoy and to share.
1. What kind of a garden for you? -- 2. Site conditions -- 3. Landscape plans for city garden -- 4. Planning a country garden -- 5. Site conditions -- 6. Landscape plans for country garden -- 7. Practical guides to garden details -- 8. Water, features, furnishings, and wildlife -- 9. My favorite plants -- 10. Planting fundamentals.
Includes index.
Keywords: GARDENS DESIGN